Coherent fibre bundles in full-field swept-source OCT - Ford, Helen D.; Tatam, Ralph P. (Cranfield University, 2009)
Endoscopic OCT probes deliver light to the measurement region via a single optical fibre mounted in a probe head. The output beam is focused onto the sample, providing a single point measurement. The beam is translated, using mechanical scanning at the probe tip, to address a line or area of sampling points and produce an image. We are investigating a swept-source OCT system incorporating coherent fibre bundles, to allow many measurement points to be addressed, within an area of the sample, without the need for mechanical motion within the endoscope probe. Scanning components are still present at the input of our system, but are no longer required within the flexible ndoscope section. This allows a small-diameter, electrically passive probe to be engineered using off-the-shelf scanning components. A common-path probe design is proposed, in which the bundle is external to the OCT interferometer. This eliminates contrast variations caused by non-controllable differences in the state of polarisation between fibres. Imaging bundle fibres are typically few-moded, which can lead to ghost features and reduced SNR in OCT images, but the common-path configuration also removes cross-mode interference problems, and reduces dispersion artefacts. OCT images of a microscope cover-slip and a sample of spring onion, acquired using the swept-source, bundle-based OCT system are presented. Features peculiar to the inclusion of the fibre bundle are discussed, and directions for future development of the system are outlined.
Keywords: Coherent fibre bundles, imaging bundles, OCT, optical fibre sensing